Post-scabies sterile plantar pustules with hypopion. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2008)
In children aged less than 1 year scabies affects sites usually spared in the adult. The plantar region is the most typical of these sites and in the newborn it is sometimes the first affected site. Besides the specific and typical lesions of scabies, in this site there can be, mainly after the regression of scabies, uninhabited blisters and pustules, that do not respond to the specific treatment -post-scabies sterile pustules-. These lesions should be differentiated from those ones of infantile acropustulosis. Moreover, a careful retrospective history of cases diagnosed as infantile acropustulosis puts in evidence in most cases a history of previous scabies (1), so that some Authors (2) wonder whether acropustulosis is a sequela of scabies. The pustular lesions respond to topical corticosteroids (1).